Nilai Budaya Podcast Cerita Rakyat Asal-Usul Nama Desa di Kabupaten Cirebon Serta Pemanfaatannya Sebagai Media Pembelajaran - Herawati, Lilik (Aksara, 2024)
Nowadays the development of technology and information is growing rapidly along with the progress of the times, including in the digital world. This study aims to describe digital literacy- based folklore by utilizing podcast media as a medium for learning digital literature. This study uses a descriptive qualitative approach. The Folklore Book About the Origin of Village Names in Cirebon Regency was used as a data source. In collecting data using the method of documentation, content analysis, questionnaires, and observation. The results of the research show that there are cultural values in the book after the study is carried out. This study is based on Kluckhohn's framework of the five basic traits in life that determine human cultural values, such as deliberation, decency, responsibility, and others. One of the most frequent topics is “The Nature of Human Relations with Others (MM)” which is related to the transmission or ecranization of folklore into podcasts that are produced using the Anchor application. The ecranization that occurred was that the book media developed into a digital podcast. The original form of folklore which only consisted of writing or text which later developed into an audio format with musical illustrations that can be accessed digitally. The validation results of media experts show that the media's average rating is 90. This score can be categorized as "Good". In addition, the Cirebon Regency folklore podcast about the origins of village names can be used as a medium for learning literature. Cirebon Regency students gave a response of 77.65% to the use of podcasts. Based on these results, it is included in the very good category.